Undone - Cat Clarke (London Quercus, 2013)
em Halliday is in love with her gay best friend. Not exactly ideal, but she's living with it. The the unspeakable happens. Kai is outed online ... and he kills himself. Jem knows nothing she can say or do will bring him back. But she wants to know who was responsible. And she wants to take them down
Keywords: story